Employment opportunities and job accessibility of disabled persons: an analysis of the law and practice in selected jurisdictions - Ali Mohamed, Ashgar Ali; Ahmad, Muhammad Hassan (Lexis Nexis Malaysia Sdn Bhd, 2021)
In general, employers are not keen to hire or retain persons with disabilities by giving various reasons. On the other hand, it is a universally recognised principle that all persons must be given equal opportunity to engage in gainful employment and this should include the disable persons. In view of that many jurisdictions across the globe passed legislations to ensure the employment of persons with disabilities and protect them from discrimination on the grounds of their disabilities in employment. Accordingly, this paper aims at evaluating the employment opportunities and job accessibility available to disabled persons mainly under Malaysian laws and briefly in selected jurisdictions such as the United Kingdom (UK), the United States (US) and Canada. It is found that albeit the Malaysian Persons with Disabilities Act 2008 advocates for better employment opportunities and accessibility of disabled employees, the Act however have not adopted words such as ‘discriminate’ or ‘protection of persons with disability against discrimination’. Therefore, it is proposed that there is a need to legislate a workplace discrimination law which should prohibit inter alia, discrimination against the disabled persons either when seeking employment or in the workplace. In addition, there is an urgent need to amend art 8(2) of the Malaysian Federal Constitution, firstly, to explicitly prohibit discrimination on the grounds of disability, and secondly, to extend its application to employees in all sectors regardless of whether it is public and private sector. Finally, it is suggested that the Malaysian government should initiate Wage Subsidy Programs to encourage the employment of persons with disability